Peer to Peer Lending Against Ease of Business Technology Acceptance Model (TAM) Approach - Djaakum, Cita Sary (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2019)
Abstract: The progress of the times will always go hand in hand with technological developments. The presence of the disruptive era encouraged the financial industry to innovate. Peer to Peer Lending (P2P Lending) is an online digital platform based alternative lending, which brings together lenders (investors) and borrowers in the marketplace. This study aims to see whether the presence of P2P Lending provides business convenience for lenders with reference to user satisfaction. The approach taken by using the Technology Acceptance Model (TAM) with Structural Equation Modeling (SEM). The results show that all variables consisting of User Perception directly influence Ease and Attitude Perception, Ease Perception directly influences Attitude and Satisfaction; and Perception of Use has an indirect effect on satisfaction with quasy mediation. Therefore, 55% of respondents stated that P2P Lending provides convenience in doing business.Abstrak: Kemajuan jaman akan selalu beriringan dengan perkembangan teknologi. Hadirnya disruptive era mendorong industri keuangan untuk melakukan inovasi. Peer to Peer Lending (P2P Lending) merupakan alternatif digital lending berbasis platform online, yang mempertemukan lender (investor) dan borrower dalam market place. Penelitian ini bertujuan untuk melihat apakah hadirnya P2P Lending memberikan kemudahan bisnis bagi Lender dengan referensi kepuasan pengguna. Pendekatan yang dilakukan dengan menggunakan Technologi Acceptance Model (TAM) dengan Structural Equation Modelling (SEM). Hasil menunjukkan bahwa seluruh variabel yang terdiri dari Persepsi Pengguna berpengaruh langsung terhadap Persepsi Kemudahan dan Sikap, Persepsi Kemudahan berpengaruh langsung terhadap Sikap dan Kepuasan; serta Persepsi Penggunaan berpengaruh tidak langsung terhadap Kepuasan dengan sifat quasy mediation. Olah karenanya, 55% responden menyatakan bahwa P2P Lending memberikan kemudahan dalam berbisnis.